Assessment of the telecommunication services sector in CARICOM : convergence issues at the regional and international level - Stern, Peter A. (CRNM [Christ Church]BB, 2007)
Analyzes the market opening in telecommunications that has occured in CARICOM states since the GATS came into force and to assess the implications for negotiations at the bilateral, regional and multilateral levels.